Empirical typology of adolescent personality organization. (July 2018) - Biberdzic, Marko; Ensink, Karin; Normandin, Lina; Clarkin, John F.
Abstract: The concept of personality organization (PO) is central to current psychodynamic understanding of normal personality development as well as the development of personality disorders (PDs). However, individual differences in PO have primarily been studied in adult populations, and it remains unclear whether the clinical indicators of normal, neurotic and borderline PO manifest differently during adolescence. This study aimed to address the gaps in current knowledge regarding the potentially different manifestation of pathological PO in adolescence. In addition, we wanted to further establish the validity of the adolescent version of the Inventory of Personality Organization, by identifying cut-off points for each of the main dimensions of Normal, Neurotic, and Borderline PO. Participants included 430 adolescents (M = 16 years old) from the community. Cluster analysis identified three levels of PO corresponding to Normal, Neurotic, and Borderline PO. Cut- off points between the different POs were successfully established using ROC curve analyses.